SOLIDARITAS PRAKTISI KUDA KEPANG PADA KOMUNITAS JAWA MUSLIM DI KELURAHAN TERJUN KECAMATAN MEDAN MARELAN - Manurung, Habib Ahmad; Syahminan, Mhd.; Muary, Rholand (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2024)
This research aims to explore the dynamics of solidarity within the Banyumasan Kencono Krido Budoyo community, particulary among its practitioners, and the factors the contribute to building solidarity within the community. The research employed a qualitative approach, utilizing data collection techquines such as observation, in-depth interviews, and documentation. The gathered and processed data were presented decriptively to draw conclusions. The findings indicate that effective communication, activities beyond the art of “kuda kepang” (a traditional Javanese horse dance), the desire to preserve the art, and religious factors play crucial roles in mainting solidarity. Internal factors such as shared traditions. Common goals, and practitioners enthusiasm, combined with community support and collaboration with other associations, furter strengthen the bonds within the “Paguyuban Banyumasan Kencono Krido Budoyo” horse dance community. All these elements unite preserve unity and solidarity within the society.